AN EVALUATIVE STUDY ON ABILITY GROUPING-BASED ENGLISH LANGUAGE TEACHING AT POLITEKNIK LP3I JAKARTA USING CIPP MODEL - Herdiana; Diand Mardiana (JOLADU: Journal of Language Education, 2022)
The objectives of the study were to investigate evaluatively the implementation of grouping-based English Language Teaching by Politeknik LP3I Jakarta, Pasar Minggu Campus. The study was held qualitatively with the participants of students and English lecturers at the Campus. The data were gained by observations, focus group discussion, and document analysis on the framework of CIPP (Context, Input, Process, Product). The data were analyzed through data collection, data display, data reduction, and the conclusion. The results reveal that the grouping is applicable although some challenges arise, particularly in teaching lower-level groups. The lower the level the more the efforts the lecturers need to adjust. This direct to conclude that the roles of lecturers in this grouping-based English language teaching are profound.